2015
DOI: 10.1002/ece3.1522
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors prevail over dispersal constraints in determining the distribution and assembly of Trichoptera species in mountain lakes

Abstract: Aiming to elucidate whether large-scale dispersal factors or environmental species sorting prevail in determining patterns of Trichoptera species composition in mountain lakes, we analyzed the distribution and assembly of the most common Trichoptera (Plectrocnemia laetabilis, Polycentropus flavomaculatus, Drusus rectus, Annitella pyrenaea, and Mystacides azurea) in the mountain lakes of the Pyrenees (Spain, France, Andorra) based on a survey of 82 lakes covering the geographical and environmental extremes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Consequently, the influence of environmental filtering increases as more isolated communities are more strongly structured by local environmental factors (Brown and Swan, 2010;Cañedo-Argüelles et al, 2015). Studies focused on European high mountain lakes, which are more isolated than high mountain streams and rivers, have found that local environmental factors are more important in structuring macroinvertebrate communities than spatial factors (Kernan et al, 2009;de Mendoza and Catalan, 2010;de Mendoza et al, 2015). On the lake-connected aspect of the Cangshan Mountain, the interaction between dispersal and environmental filtering on river metacommunities has been altered compared to the river-connected aspect.…”
Section: Influence Of Connectivity On Dispersal and Metacommunitiesmentioning
confidence: 99%
“…Consequently, the influence of environmental filtering increases as more isolated communities are more strongly structured by local environmental factors (Brown and Swan, 2010;Cañedo-Argüelles et al, 2015). Studies focused on European high mountain lakes, which are more isolated than high mountain streams and rivers, have found that local environmental factors are more important in structuring macroinvertebrate communities than spatial factors (Kernan et al, 2009;de Mendoza and Catalan, 2010;de Mendoza et al, 2015). On the lake-connected aspect of the Cangshan Mountain, the interaction between dispersal and environmental filtering on river metacommunities has been altered compared to the river-connected aspect.…”
Section: Influence Of Connectivity On Dispersal and Metacommunitiesmentioning
confidence: 99%
“…niche position and niche breadth) have also formerly been found as significant correlates of the degree of site occupancy in stream insects (Heino , Siqueira et al , Verberk et al , Heino and Grönroos ). In particular, we tested 1) whether different species show independent responses to environmental, spatial and geographic variables at a regional scale (de Mendoza et al ); 2) whether ecological and biological traits explain variation in the accuracy of models predicting species distributions; and 3) whether species niche characteristics explain variation among species in model performance, because these variables are related to the degree of occupancy in stream insects (Heino ) and other groups of organisms (Slatyer et al ).…”
mentioning
confidence: 99%
“…4,000 individuals) were mounted on slides with glycerine, the preparations sealed with paraffin, and species determined under the microscope following mainly Abebe, Andrássy, and Traunspurger (). Taxonomic determination of oligochaetes was performed in a previous study (Collado & de Mendoza, ), as well as that of some insect groups such as Coleoptera (de Mendoza, Rico, & Catalan, ) and Trichoptera (de Mendoza, Ventura, & Catalan, ). Chironomids were determined as part of a separate manuscript in preparation (G. de Mendoza, M. Rieradevall and J. Catalan, unpublished manuscript ).…”
Section: Methodsmentioning
confidence: 99%